Genome- and transcriptome-wide off-target analyses of an improved cytosine base editor. Issue 1 (7th June 2021) - Randall, Linnell Bentley; Sretenovic, Simon; Wu, Yuechao; Yin, Desuo; Zhang, Tao; Eck, Joyce Van; Qi, Yiping
Abstract: Cytosine base editors (CBEs) are the promising tools for precise genome editing in plants. It is important to investigate potential off-target effects of an efficient CBE at the genome and transcriptome levels in a major crop. Based on comparison of five cytidine deaminases and two different promoters for expressing single-guide RNAs (sgRNAs), we tested a highly efficient A3A/Y130F-BE3 system for efficient C-to-T base editing in tomato ( Solanum lycopersicum ). We then conducted whole-genome sequencing of four base-edited tomato plants, three Green fluorescent protein (GFP)-expressing control plants, and two wild-type plants. The sequencing depths ranged from 25× to 49× with read mapping rates >97%. No sgRNA-dependent off-target mutations were detected. Our data show an average of approximately 1, 000 single-nucleotide variations (SNVs) and approximately 100 insertions and deletions (indels) per GFP control plant. Base-edited plants had on average elevated levels of SNVs (approximately 1, 250) and indels (approximately 300) per plant. On average, about 200 more C-to-T (G-to-A) mutations were found in a base-edited plant than a GFP control plant, suggesting some level of sgRNA-independent off-target effects, though the difference is not statistically significant. We also conducted RNA sequencing of the same four base-edited plants and three GFP control plants. An average of approximately 200 RNA SNVs was discovered per plant for either base-edited or GFP control plants. Furthermore, no specific enrichment of C-to-U mutations can be found in the base-edited plants. Hence, we cannot find any evidence for bona fide off-target mutations by A3A/Y130F-BE3 at the transcriptome level. Abstract : Whole-genome sequencing and transcriptome sequencing reveal high editing specificity of an improved cytosine base editor in tomato.